2014
DOI: 10.15835/nbha4229607
|View full text |Cite
|
Sign up to set email alerts
|

Minor Volatile Compounds in Traditional Homemade Fruit Brandies from Transylvania-Romania, as Determined by GC-MS Analysis

Abstract: In order to investigate the minor volatile compounds of traditional homemade fruit brandies from Romania (Transylvania region), as a result of their assortment and provenience, a number of 26 samples (18 plum brandies samples from 3 different counties, 4 samples of apple brandy and 4 samples of pear brandy) were analyzed using liquid-liquid extraction and gas-chromatography coupled with mass-spectrometry (GC-MS) technique. The GC-MS chromatograms of the hexane extracts led to the identification of 34 compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…The volatile components in fruit brandies were analyzed by gas chromatography (GC) with a flame-ionization detector (FID) by direct injection into the gas chromatograph column using the method adapted from European Union reference method for volatile compounds [23] considering the recommendations and conclusions of similar studies [16,[24][25].…”
Section: Physico-chemical Analysis Of Distillatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The volatile components in fruit brandies were analyzed by gas chromatography (GC) with a flame-ionization detector (FID) by direct injection into the gas chromatograph column using the method adapted from European Union reference method for volatile compounds [23] considering the recommendations and conclusions of similar studies [16,[24][25].…”
Section: Physico-chemical Analysis Of Distillatesmentioning
confidence: 99%
“…The analysis of fruit brandy (spirit) manufactured by traditional methods in European countries was the subject of several papers [4,5,16]. The analysis of these types of beverages has a significant importance in the authentication, control and prevention of fraud [16]. However, the details regarding the manufacturing stages are less described.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies found on the compositions of volatile compounds in fruit spirits, such as plum brandy 1 , 2 , pear brandy 3 , apricot brandy 4 , apple brandy 5 , mirabelle brandy 6 or raspberry brandy 7 . Some of them also dealt with the comparison of aromatic compounds in different kinds of fruit spirits 5 , 8 . Characteristic compounds for FS are esters (typically ethylesters such as ethyl caprylate, ethyl caprate, ethyl laurate, ethyl myristate, ethyl palmitate and others) which are common for many types of FS and form dominant part of aroma profile 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The volatile compounds are responsible for the quality and safety of spirits, depending on their composition, concentration and sensorial properties, essential for customer's acceptance. 4 Phenolic compounds and volatiles that give specific aroma to spirit drinks can be used to classify these drinks by type, origin, country and even provenience region. 4 The widely used method for the phenolic and volatile compounds analysis is chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…4 Phenolic compounds and volatiles that give specific aroma to spirit drinks can be used to classify these drinks by type, origin, country and even provenience region. 4 The widely used method for the phenolic and volatile compounds analysis is chromatography. 5 Prior to chromatographic analysis which are time-consuming, relatively expensive and require skilled personnel, various extraction methods have been widely used, such as liquid-liquid extraction.…”
Section: Introductionmentioning
confidence: 99%